KAJIAN YURIDIS PENYELESAIAN WANPRESTASI PADA KONTRAK ANTARA PEMAIN SEPAK BOLA PROFESIONAL DENGAN KLUB PERSIBA BANTUL - Priambada, Erwan; Imanullah, Moch. Najib (Fakultas Hukum Universitas Sebelas Maret, 2017)
AbstractThis legal writing analysis, describe, and examine the forms of legal protection of professional soccer players in case of tort in the form of delinquent payment by the person who manages a football club Persiba Bantul and finishing the tort be in arrears Football Club players salary Persiba Bantul that